Growth Response of Two Cowpea Varieties to the Allelopathic Effects of Azadirachta indica (A. Juss) Bark Extract - Etuwoma, Patience Onize; Omakor, Ichehoke Austine (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
The aim of this study was to evaluate the growth response of two varieties of Cowpea – Vigna unguiculata (SAMPEA 7 and IT97K-499-35) to the bark extract of Azadirachta indica. The crop plant was exposed to varying concentrations of 100, 75, 50, and 25 g/L of the aqueous stem bark extract using a Complete Randomised Block Design. There were three replications per treatment, of which three were randomly selected for further analysis. The study lasted 10 days. Data was collected on Germination percentage, root length, shoot length and fresh weight. Data were analysed using ANOVA at the 5% significance level, and DMRT was used to rank the means. The results revealed the susceptibility of the two cowpea varieties to the stem bark extract of A. indica, in a concentration-dependent manner, with respect to germination percentage, root and shoot length, and seedling fresh weight. The overall germination and growth rate of seedlings were reduced with the 100 g/L neem stem bark extract treatment, followed by 75 g/L, then 50 g/L; the least was 25 g/L. Variety IT97K-499-35 showed more susceptibility to the treatments. This suggests that A. indica exhibits an allelopathic effect on the examined types and can therefore serve as a biological means of weed control, as natural substances are regarded as more environmentally benign than most synthetic herbicides.